Interaction Study of Glass Sealents and Electrolyte of Solid Oxide Fuel Cell - Sharma, Sarita Devi (My University, 2008)
The chemical interactions between different SrO-SiO2-B2O3-A2O3 {A= Y, La, Al and Cr) based glass sealants and Bi4V1.8Al0.2O11 electrolyte are investigated. The glass and electrolyte are taken in 3:1 wt% respectively. Mixture of these components were heat treated for different time durations and then characterized by X-Ray diffraction (XRD), Fourier Transform Infra Red spectroscopy (FTIR) and dilatometer, to determine the possible reaction phases their volume fraction and prominent band formation. During heat treatment main phases formed were SrVSi2O7, AlVO4, YVO4, Cr2SiO4. The volume fraction of the various phases depends on the Al2O3, Y2O3, Y2O3 and Cr2O3 along with heat treatment durations. The FTIR spectra of all the samples exhibit three bands i ,e 400-600 cm-1, 650-800 cm-1 and 800- 1300 cm-1 . These spectra are assigned to bending vibrations of the Si-0-Si linkages, bending vibrations of the A-O (A= Y, La, Al and Cr) bonds and stretching vibrations of the SiO4 tetrahedron with the different numbers of bridging oxygen atoms. The thermal expansion coefficient of diffusion couple is 8X 10-6/°C which is very close to desired value of SOFC.
M.Tech.(Guide)
Keywords: Glasses; SOFC